Transcriptome Analysis Revealed Hub Genes Related to Tipburn Resistance in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Yaning Bi; Wenjing Zhang; Yuxiang Yuan; Jianqi Feng; Peiyun Wang; Cong Ding; Yanyan Zhao; Lin Li; Henan Su; Baoming Tian; Fang Wei; Xiaochun Wei; et al. (Plants)
Tipburn is a physiological disease in Chinese cabbage. In recent years, this disease has become increasingly serious, affecting the quality and economic benefits of Chinese cabbage. However, little is known about the molecular mechanism by which calcium deficiency induces tipburn. Therefore, we performed transcriptome analysis on Y578-2 (tipburn-resistant accession) and Y920-2 (tipburn-susceptible accession) to identify the genes involved in the tipburn defense mechanism in Chinese cabbage. In this study, phenotypic observation showed that Y920-2 began to display symptoms on the 10th day of calcium deficiency treatment. Through weighted gene co-expression network analysis (WGCNA), three gene modules that were highly related to tipburn resistance were identified. Analysis of gene expression regulation in the three modules revealed 13 hub genes related to tipburn resistance, which were involved in the cell wall, photosynthesis, transcription factors, hormones, and the stress response, indicating that these factors play an important role in the tipburn response of Chinese cabbage. These transcriptome data and analysis results provide a basis for the study of the molecular mechanism of calcium deficiency-induced tipburn in Chinese cabbage.